Transplantasi Organ Tubuh dalam Perpektif Yuridis - Nisa, Afifatin; Safitri, Yuni (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the legal consequences of organ transplants made according to a special agreement before a notary. The research used a normative juridical approach. The approach used in this research was the statutory approach and the conceptual approach. The legal consequences over the commercialization of body organs with the private deed were null and void because the law did not fulfill the objective requirements for the agreement's validity. The denial of the related notarial deed regarding organ transplantation did not result in a claim for compensation because it was considered that an agreement had never been made.